The Identification of Research Priority in The Field of Food Security - Budi Triyono; Chichi Sinthia Laksani; Muhammad Zulhamdani; Irene Muflikh Nadhiroh; Lutfah Ariana (Publisher of Widyagama University of Malang (UWG Press), 2018)
The development of food security in Indonesia still faces various problems. Dealing with those problems, the role of research and development institutions such as the Indonesia Institute of Sciences (LIPI) is needed. LIPI as a government R & D institution is expected not only to produce knowledge, but also to play an active role in solving various problems of the nation including in the field of food security. The results of the evaluation of LIPI's activities show that it has produced significant and strategic research outputs. However, only a few have been successfully implemented to solve food problems. Therefore, a study of Research Priority Setting (RPS) is needed so that the LIPI research activities program in the future will produce more research outputs that play a role in providing solutions in this food sector. The purpose of this RPS study is to provide direction so that LIPI research in the future can contribute more to solving problems in the food sector. This study starts from the activity stage to identify strategic issues that need to be resolved through R & D activities. This identification activity is carried out through a round table discussion involving stakeholders. The next stage is to determine researches that need to be prioritized by LIPI in the next five years using the Delphi method. From the study, it is concluded that in the next five years LIPI's R & D activities should be focused on: (1) the development of biological organic fertilizer, (2) the development of local food materials, (3) the development of Germplasm, (4) the functional food development, and (5) the development of modern agriculture. JEL Classification: D24, L26, Q12